2021
DOI: 10.1038/s41598-021-96482-6
|View full text |Cite
|
Sign up to set email alerts
|

Two Nicotiana occidentalis accessions enable gene identification for Type II hybrid lethality by the cross to N. sylvestris

Abstract: Hybrid lethality, meaning the death of F1 hybrid seedlings, has been observed in many plant species, including Nicotiana. Previously, we have revealed that hybrids of the selected Nicotiana occidentalis accession and N. tabacum, an allotetraploid with S and T genomes, exhibited lethality characterized by the fading of shoot color. The lethality was suggested to be controlled by alleles of loci on the S and T genomes derived from N. sylvestris and N. tomentosiformis, respectively. Here, we extended the analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Conspecific pollen precedence and gametic incompatibility are examples of post-mating prezygotic isolating barriers ( Rieseberg and Willis, 2007 ). In turn, postzygotic isolation barriers include enlarged ovary (immature fruit) abscission ( Gupta et al, 1996 ; He et al, 2019 ), seed abortion or hybrid seed lethality ( Coughlan et al, 2020 ; Dziasek et al, 2021 ), hybrid weakness ( Shiragaki et al, 2019 , 2020 ), hybrid lethality ( Kawaguchi et al, 2021 ; Si et al, 2021 ; Tezuka et al, 2021 ; Mino et al, 2022 ), and hybrid sterility ( Li et al, 2020 ) in seedlings of the F 1 generation, as well as hybrid breakdown recognized in generations after the F 1 ( Matsubara et al, 2007 ; Zhang et al, 2021 ). These isolating barriers may be observed independently or combined, even in a single cross-combination.…”
Section: Introductionmentioning
confidence: 99%
“…Conspecific pollen precedence and gametic incompatibility are examples of post-mating prezygotic isolating barriers ( Rieseberg and Willis, 2007 ). In turn, postzygotic isolation barriers include enlarged ovary (immature fruit) abscission ( Gupta et al, 1996 ; He et al, 2019 ), seed abortion or hybrid seed lethality ( Coughlan et al, 2020 ; Dziasek et al, 2021 ), hybrid weakness ( Shiragaki et al, 2019 , 2020 ), hybrid lethality ( Kawaguchi et al, 2021 ; Si et al, 2021 ; Tezuka et al, 2021 ; Mino et al, 2022 ), and hybrid sterility ( Li et al, 2020 ) in seedlings of the F 1 generation, as well as hybrid breakdown recognized in generations after the F 1 ( Matsubara et al, 2007 ; Zhang et al, 2021 ). These isolating barriers may be observed independently or combined, even in a single cross-combination.…”
Section: Introductionmentioning
confidence: 99%
“…Conspecific pollen precedence and gametic incompatibility are examples of post-mating prezygotic isolating barriers . In turn, postzygotic isolation barriers include enlarged ovary (immature fruit) abscission (Gupta et al, 1996;He et al, 2019), seed abortion or hybrid seed lethality (Coughlan et al, 2020;Dziasek et al, 2021), hybrid weakness (Shiragaki et al, 2019(Shiragaki et al, , 2020, hybrid lethality (Kawaguchi et al, 2021;Si et al, 2021;Tezuka et al, 2021 , and hybrid sterility in seedlings of the F 1 generation, as well as hybrid breakdown recognized in generations after the F 1 (Matsubara et al, 2007;. These isolating barriers may be observed independently or combined, even in a single cross-combination.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid lethality in Nicotiana is thought to be caused by epistatic interactions between alleles at different loci [18,35]. Previous studies have demonstrated that the Q chromosome of the S genome in N. tabacum has gene(s) that cause hybrid lethality [17,20,36,37].…”
Section: Introductionmentioning
confidence: 99%